Pengaruh Kompensasi, Lingkungan Kerja, Dan Gaya Kepemimpinan Terhadap Turnover Intention Karyawan Pada PT. Royal Inti Mandiri Abadi (Studi Pada Bagian Divisi Marketing and Sales) - Kurniawan, Eunike Ivani; Erdiana, Atty (PRAGMATIS, 2024)
This research aims to determine the influence of compensation variables, work environment, and leadership style on turnover intention among PT employees. Royal Inti Mandiri Abadi. This research was conducted based on the problem that in this company every year the average rate of employees leaving is relatively higher than employees entering. This needs to be a special concern for companies to reduce the risk of increasingly high employee turnover intention. The employee turnover rate shows the level of employee desire to move to a better place. The independent variables in this research are compensation, work environment, and leadership style, while the dependent variable in this research is turnover intention. This research uses quantitative research methods. Data collection was carried out by distributing questionnaires to thirty-two respondents who worked in the marketing and sales departments. The data analysis contained in this research is multiple linear regression analysis using the SPSS program. The results of this study state that compensation, work environment, and leadership style have a significant effect on turnover intention. From this research, it is hoped that companies can provide and maintain compensation according to workload, ensure a safe and comfortable work environment, and use the right leadership style so that they can increase turnover rates among PT employees. Low Immortal Core Royalty